2021
DOI: 10.3390/ijms22179111
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin Depletion Induces Inflammation in the Bone Marrow of Mice

Abstract: Romosozumab, a humanized monoclonal antibody specific for sclerostin (SOST), has been approved for treatment of postmenopausal women with osteoporosis at a high risk for fracture. Previous work in sclerostin global knockout (Sost−/−) mice indicated alterations in immune cell development in the bone marrow (BM), which could be a possible side effect in romosozumab-treated patients. Here, we examined the effects of short-term sclerostin depletion in the BM on hematopoiesis in young mice receiving sclerostin anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 102 publications
(125 reference statements)
1
6
0
Order By: Relevance
“…SOST overexpression or administration of recombinant mouse SOST prevented AAA development [39,56]. Our study also established a new role for SOST in controlling aortic SMC phenotype modulation by reducing β-catenin nuclear translocation in addition to SOST's effects on inflammation [39,57,58]. Moreover, we showed that activation of the WNT singling using WNT agonist 1 upregulated KLF4 expression.…”
Section: Discussionsupporting
confidence: 57%
“…SOST overexpression or administration of recombinant mouse SOST prevented AAA development [39,56]. Our study also established a new role for SOST in controlling aortic SMC phenotype modulation by reducing β-catenin nuclear translocation in addition to SOST's effects on inflammation [39,57,58]. Moreover, we showed that activation of the WNT singling using WNT agonist 1 upregulated KLF4 expression.…”
Section: Discussionsupporting
confidence: 57%
“…Studies on Sost −/− recipient mice have demonstrated for SOST an inhibitory effect on proliferation and mobilization of myeloid progenitor. These suppression mechanisms would involve lymphoid cell also [ 30 ] and potentially platelet count. A positive correlation between SOST levels and platelets count was indeed observed here.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that short-term depletion of sclerostin alters immune cell development in the BM and spleen. 147 In addition, depletion of sclerostin correlates with enhanced levels of inflammatory cytokines such as MCP-1, TNF-α, etc, 147 thereby, questioning the employment of sclerostin in postmenopausal osteoporotic patients. Thus, in search for a safe, novel, and cost-effective therapeutic strategy our group along with other’s have reported that probiotics exhibit immunoporotic potential, thereby enhancing bone health in several bone anomalies including osteoporosis.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%